Plotinus's Notion of Procession - Zamora, José María (1997)
The A. interprets Piotinus's Enneads starting from the notion of procession, key element for understanding the architecture of the Plotinian universe hierarchical lyordered around the One-Good. From the first principie proceed all other beings that converge in him. Four aspects are mainly examined: 1) The axiom of the procession. 2) The two moments of the procession: the ascendent and the descendent. 3) The images of the procession.4) Among these metaphors, he favours the centre and the circle, core of the analysis of the notion of procession.